The Structural Plan’s sustainability in coastal areas. A case study in the Tyrrhenian coast of Calabria - Chieffallo, Lucia; Palermo, Annunziata; Viapiana, Maria Francesca (TeMA - Journal of Land Use, Mobility and Environment, 2022)
Sustainable planning in coastal areas must integrate environmental protection actions and development actions addressing settlement policies and the location of functional and tourist infrastructure and services that are particularly relevant from a socio-economic point of view. In Italy, coastal planning is fragmented between state, regional and municipal competences. All Italian municipalities have the task of drafting the plan that outlines the strategic scenarios and the structural choices for the governance of the territory under their jurisdiction. We therefore wonder how this general plan can incorporate the specificities of coastal territories starting from the elaboration of the knowledge framework to define a sustainable plan project. To answer this question, we focus on the Calabrian regional territory, which hosts 10% of the national coastal heritage. The paper presents and discusses the procedural and content aspects related to the elaboration of the Preliminary Document of the Structural Plan of a municipality located on the coast of the Tyrrhenian Sea to draw general conclusions from the local experience useful for planners.